Informed consent : information production and ideology - Schiff, Lisa R., 1966- (Scarecrow Press, 2003)
"Informed Consent analyzes the interplay between ideology and information. Through extensive research on how information about the homeless is generated and interpreted, Lisa R. Schiff offers both hard evidence and a convincing argument for questioning "how service providers create forms and clients complete them, how advocates administer surveys and public agencies compile counts." At the same time, she explores the day-to-day implications of her findings by demonstrating how competing understandings affect prevailing ideologies, which in turn affect our attempts at social change."--Jacket